Advergames: WoMo viral action (“Word of Mouse”) - Sandra Oliveira (Estudos em Comunicação, 2012)
The transformation felt today among the Internet is creating a new paradigm for communication channels in general and in particular for advertising communication. If we combine the sense that the decline in recent years in advertising spending in traditional media, we found a turning point in how the communication re-aches the potential consumers. And consequently how it is distributed. In this sense, the study attempts to understand how today’s consumer, before this transformation, moves and how it is inﬂuenced and inﬂuences the advertising strategy of a brand. We understand that today we ﬁnd a consumer who is increasingly involved in internet communication and distribution of information and relationships. Although the performance of brands follows the trends, the study described here also wants to see how the tools can help webmarketing, draw the consumer’s attention and basically take you to positive action. Consequently, the strategy of brands has become the place to give what is called "Brand Entertainment."This concept has created a new way for brands can reach consumers in an informal way, as it means the inclusion of advertisements in the content demanded by consumers. And one of the most known are Advergames, games created for brands that provide advertising spend fun. We understand that the growing implementation of advertising strategies in Advergames brands can create involvement by your target audience. Studies such as Wise et al (2008) show the positive effect of using this type of medium. The authors found advantages in the use of Advergames in regarding to the relationship established between mark and player. Freitas (s / d) believes are beneﬁcial for ﬁxing and awareness of the brand or product and, ulti- mately, help brands to create loyalty and rememberance. This type of advertising has strong acceptance and is considered less intrusive by nature, but strongly associated with the entertainment game. With these factors combined, the effect of Advergame can be achieved by creating the player feeling of immersion, through entertainment and commitment. The request made consumer attention is so striking achieved that which is detrimental to the viewing application, for example a television commercial of 30 seconds. The indicated effects are likely to generate meaning and relation creating due to the amount of time that the consumer is exposed to brand message. If we put the fun time of interaction with the branded product, then we can be creating retention and brand image in the background positive attitude towards it. ("Brand Awareness’) The study also looks at how the Advergames can prolong the feeling of gratiﬁcation and distribute this knowledge. We therefore support the study of phenomena such as the "Word of Mouse"(Womo), ie, in a way that the consumer can distribute advertising content in your social network online and ofﬂine explaining the fun that got on your blog, promoting on Twitter, etc..